Analisis Kriminologi Victim Precipitation dalam Kasus Kekerasan Seksual terhadap Pekerja Seks - Vicky Yohanes Posumah; Muhammad Rizal Rustam (Decisio: Jurnal Ilmiah Hukum, 2025)
Sex workers are often victims of sexual violence due to stigma, discrimination, and a lack of legal protection. Despite the perception that their profession is deviant, many individuals engage in sex work due to economic pressures and limited employment opportunities. The concept of victim precipitation in criminology examines the role of victims in triggering crimes, which is often misinterpreted as victim-blaming in cases of sexual violence against sex workers. This study aims to analyze how victim precipitation influences sexual violence against sex workers and its implications in the legal system. This research employs a qualitative approach with normative legal analysis, utilizing primary legal materials such as laws, regulations, and court decisions, along with secondary sources from scholarly journals and literature. The data were collected through an extensive literature review and analyzed using a descriptive qualitative method. The findings reveal that sex workers experience high levels of sexual violence due to social stigma, economic vulnerabilities, and legal system biases. The misinterpretation of victim precipitation often leads to victim-blaming, further discouraging victims from reporting cases. Additionally, the lack of legal protection and law enforcement’s discriminatory attitudes exacerbate the issue, making sex workers more vulnerable to violence. Therefore, legal reforms and social policies are needed to provide equal protection and justice for sex workers as victims of sexual violence.